Ultrasound Imaging for Muscle Variations: Digastric Flexor Carpi Ulnaris, Gastrocnemius Tertius, and Supernumerary Fibularis Longus in an Asymptomatic Family. (November 2018) - Ata, Ayşe Merve; Kara, Murat; Aydin, Gülümser; Kaymak, Bayram; Gürçay, Eda; Özçakar, Levent
Abstract : Abstract: Anatomical variations of the muscles are seen with different frequencies. Although most of them are asymptomatic; in certain cases, their existence requires attention with regard to entrapment syndromes, mass lesions, botulinum toxin injections, and tendon transfers. Herein, as ultrasound imaging is a convenient method for muscle imaging, it can easily be used in daily practice for prompt understanding of such muscular variations. In this report, we demonstrated and discussed a similar scenario in an asymptomatic individual (and his close family members) using ultrasound imaging for scanning the digastric flexor carpi ulnaris, gastrocnemius tertius, and supernumerary fibularis longus muscles. Abstract : Supplemental digital content is available in the text.